Level of the External Auditor’s Reliance Decision on the Internal Auditors Function as a Management Training Ground - Vahid Mennati; Okhtharoon Alipour (مطالعات تجربی حسابداری مالی, 2021)
Objectivity is one of the four fundamental principles of internal auditors Code of Ethics. In 2010, The Institute of Internal Auditors (IIA) introduced the Value Proposition and objectivity is one of the three core elements of it. Also, according to Auditing Standard No. 610, objectivity is one of the main components of internal auditing. Use of internal Audit Function (IAF) as a Management Training Ground (MTG) is in companies that internal auditors are promoted to executive positions. This can impair their objectivity and affect the reliance of independent auditors on their work. So the purpose of this study is to investigate the level of the External Auditor’s Reliance Decision on the Internal Auditors Function as a MTG. The purpose of this study is to investigate the reliance of external auditors on the work of internal auditors according to the strategy of MTG. Participants of this study are External auditors including partners, managers, senior supervisors, and senior auditors of Iranian audit firms. In this survey, 100 questionnaires were collected. The results of the study show that external auditors perceive internal auditors employed in an IAF used as a MTG to be less objective. The results also showed that external auditors perceive the competence and due professional care of IAFs used as a MTG less than other IAFs.